(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2022)
After the government implemented the Implementation of Community Activity Restrictions (PPKM) in August 2021, COVID-19 cases in Papua Province had decreased by 46.2%. The daily average of COVID-19 cases in July decreased from 370 to 119 cases to be precise in August 2021. One of the Jayapura City government policies in early 2022 that aimed to break the chain of COVID-19 spread was to eliminate face-to-face learning for Kindergarten, Elementary, Junior High, and High School education levels from February 15 - March 15, 2022. Previous research related to the analysis of the cumulative distribution of COVID-19 in Papua province had been carried out in 2021. It used data on COVID-19 cases for two months during September 1 - October 31, 2020. The researchers used the Johnson SB model. In contrast to previous studies, the present study aimed to use the distribution of Erlang, Fatigue Life, Frechet, Gamma, Logistics, Pareto, Pearson Type 5 and Weibull to perform a cumulative and survival analysis on positive cases of COVID-19 patients in Papua Province in 2021. In addition, This study used COVID-19 data from January to April 2021. The results showed that the analysis of COVID-19 data in Papua Province in 2021 can utilize the Fatigue Life, Frechet, Gamma, Logistics, Pearson Type 5 and Weibull models.